Penerapan Kode Etik Pengelolaan Satauan Pendidikan - Maziah Maziah; CA. Astuti Darmayanti; Saprialman Saprialman (Jurnal Ilmiah Wahana Pendidikan, 2023)
The position of an education unit manager, namely the school principal, is an additional mandate given to teachers to lead. A school principal, of course, has a period in which the period lasts for four years. If he has matured for four years, his position as a school principal must end. Law No. 19 of 2005 which discusses national standards of education and based on the Decree of the Minister of National Education No. 162/U/2003 discusses a guideline for affirming an educator as an educational staff; school. Referring to the various kinds of policies that have regulated the performance development mentioned above, there are separate references before an educator occupies this position, before occupying this position he must first serve as deputy principal of the school, because an educator who has previously served as deputy principal has More value than that, which position can be beneficial for career development. Regarding matters of quality improvement for a school or educational institution, a school principal must prepare a recruitment nomination which includes education and training for prospective school principals who have certified abilities or competencies as well as school principal work assessments in accordance with the applicable code of ethics. And the problem of the workload of an educational staff manager is very heavy for them. For example, teaching assignments for six hours a week, which is actually very ineffective for a school principal, and ends up not being completed. This is very easy to understand because as a school principal, his work is not only to carry out his managerial duties, but he also has other burdens to carry. Therefore this article will discuss the application and any problems contained in the application of the code of ethics for education unit managers.